MicroRNAs in metabolic syndrome - Codocedo, Juan Francisco; Inestrosa, Nibaldo C. (My University, 2019)
Metabolic syndrome (MetS) corresponds to a cluster of several risk factors that increase the risk of other health problems, such as cardiovascular disease and diabetes. The combinatorial nature of MetS makes its etiology complex as it is determined by the interplay of both genetic and environmental factors like nutrition or physical activity. Accordingly, intricate regulatory networks have evolved to respond to changes in environmental conditions and physiological stress. In the search for key molecular pathways that could elucidate the complex physiopathology of MetS, as well as serve as therapeutic tools, microRNAs (miRNAs) have emerged as attractive molecules, given their role as important components of complex gene regulatory networks. MiRNAs typically control the expression of their target genes by imperfect base pairing to the 30 untranslated regions (30UTR) of their messenger RNAs (mRNAs) targets. Currently, several aspects of the miRNA biogenic process are known in detail, as well as the translational repression mechanisms exerted by miRNAs on their target mRNAs. The number of studies associating miRNAs with the metabolic risk factors of MetS is increasing; however, few studies directly relate miRNAs to a well-defined model of MetS. There is no doubt that miRNAs play an important role in the development of individual components of MetS; however, our understanding of their function during the different combinatorial modalities of MetS is poor. In this chapter, we review several of the studies investigating the relationship between miRNA dysfunction and MetS. We discuss the role of nutrition and genetic in the modulation of miRNAs activities and how our dietary behavior can have profound consequences in the metabolic health of our progeny.
Keywords: diabetes; epigenetics; genetic burden; high-fat diet; maternal obesity; metabolic syndrome; metabolism; micrornas; nutrition; paternal obesity; transgenerational inheritance